Cooperative supramolecular helical assembly of a pyridinium-tailored methyl glycyrrhetate. Issue 44 (24th October 2016) - Gao, Yuxia; Hao, Jie; Wu, Jindan; Li, Ying; Lin, Yuan; Hu, Jun; Ju, Yong
Abstract : A pyridinium-functionalized methyl glycyrrhetate was regulated into helices by hydrophobic forces and π–π stacking in a cooperative manner in water. Abstract : Taking a natural triterpenoid as the building block, we have regulated a pyridinium-functionalized methyl glycyrrhetate (C4-MGP) into P-type helices in water primarily driven by hydrophobic forces. By analysing their temperature-dependent CD and UV-Vis spectra, these hierarchical chiral assemblies were found to be formed in a cooperative supramolecular polymerization manner.